Analisa Faktor-Faktor yang Mempengaruhi Konsumen dalam Keputusan Pembelian Mobil Toyota di Surakarta - Roni Zakaria R; Fakhrina Fahma; Sujiyati - (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2007)
The aims of this study are: (1) To find out the influence of the culture, social, psychology and personal variables to the Toyota cars purchasing decision in Surakarta; (2) To find out the most dominant factor in influencing the Toyota-type car purchasing decision in Surakarta, so that it can be used as a consideration in making any policies in determining the marketing strategy.This study is carried out in Toyota Dealer Surakarta by using quantitative approach. The technique used in collecting data is questionnaire with 30 of sample. The analysis used is the multiple linear regression analysis. The result of this study are: (1) The contribution of the culture variable to the purchasing decision is shown by the unstandardized beta coefficient value of 0.234, which means that each increasing of culture variable will influence the purchasing decision of 0.234; (2) The contribution of the social variable to the purchasing decision is shown by the unstandradized beta coefficient value of 0.213, which means that each increasing of social variable will influence the purchasing decision of 0.213; (3) The contribution of psychology variable to the purchasing decision is shown by the unstandardized beta coefficient value of 0.164, which means that each increasing psychology variable will influence the purchasing decision of 0.164; (4) The contribution of personal variable to the purchasing decision is shown by the unstandardized beta coefficient value of 0.409, which means that each increasing personal variable will influence the purchasing decision of 0.409; and (5) The most dominant factor in influencing the purchasing decision is the personal variable, which is proved by the unstandardized beta coefficient value of 0.409, which is the highest value than of other variables.